2011
DOI: 10.1111/j.1365-2362.2011.02472.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in renin predicts the effects of thiazide diuretics

Abstract: In addition to PRA, renin rs11240688 CC polymorphism may also independently predict the effect of HCTZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
2
7
0
1
Order By: Relevance
“…The findings were in accordance with our previous findings that patients with systolic hypertension respond better to thiazide treatment than those with diastolic hypertension and lower SBP [27]. Furthermore, patients with a lower baseline renin level are associated with greater BP reduction [28], which is also compatible with the notion that patients with relatively increased arteriolar resistance and volume accumulation may have a unique response to short-term thiazide treatment.…”
Section: Discussionsupporting
confidence: 92%
“…The findings were in accordance with our previous findings that patients with systolic hypertension respond better to thiazide treatment than those with diastolic hypertension and lower SBP [27]. Furthermore, patients with a lower baseline renin level are associated with greater BP reduction [28], which is also compatible with the notion that patients with relatively increased arteriolar resistance and volume accumulation may have a unique response to short-term thiazide treatment.…”
Section: Discussionsupporting
confidence: 92%
“…This study also replicated the greater DBP response in C allele homozygotes in the small but independent cohort. An additional variant of REN, rs11240688, was associated with HCTZ-induced BP reduction 45 . It remains to be understood whether these results can be extrapolated to populations without Asian ancestry.…”
Section: Candidate Pharmacodynamic Polymorphisms Of the Renin-angiotementioning
confidence: 99%
“…Another study in 1447 hypertensive Chinese patients demonstrated that patients with the minor allele (A) of the AGT rs7079 SNP had a better blood pressure response to ACE inhibitors (benazepril) when compared to ACE users with the common allele (Su et al, 2007). Another group recently reported no difference in blood pressure response to hydrochlorothiazide associated with rs7079 (Huang et al, 2011). In sum, these studies suggest that variations in the AGT gene may have an influence on blood pressure response to antihypertensive therapies.…”
Section: Discussionmentioning
confidence: 99%